2020
DOI: 10.1097/md.0000000000020577
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome, depression, and fibromyalgia syndrome prevalence in patients with irritable bowel syndrome

Abstract: Although both metabolic syndrome (MetS) and irritable bowel syndrome (IBS) have been linked with altered gut microbiota, only a few studies investigated the association between them. Hence, we aimed to evaluate the prevalence of MetS along with depression and fibromyalgia syndrome (FMS) in IBS patients. This was a case-control study in which 3808 consecutive patients who attended outpatient clinics of Erzurum Regional Training and Research Hospital between May 2019 and August 2019 were evaluated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
2
2
0
1
Order By: Relevance
“…These findings are in line with other previous obervations in this field [18,48]. It has been postulated that link between high triglyceride levels, metabolic syndrome (MS) and IBS might exist [48,49].…”
Section: Symptomssupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are in line with other previous obervations in this field [18,48]. It has been postulated that link between high triglyceride levels, metabolic syndrome (MS) and IBS might exist [48,49].…”
Section: Symptomssupporting
confidence: 92%
“…These findings are in line with other previous obervations in this field [18,48]. It has been postulated that link between high triglyceride levels, metabolic syndrome (MS) and IBS might exist [48,49]. A previous report study Functional Foods in Health and Disease 2023; 13(2): 82-96 has already indicated that IBS might be associated with elevated triglyceride levels [18].…”
Section: Symptomssupporting
confidence: 90%
“…IBS was possibly positively associated with metabolic syndrome due to the shared pathophysiology. The alteration of gut microflora was the potential mechanism between IBS and metabolic syndrome ( Guo et al, 2014 ; Bayrak, 2020 ). Imbalance gut microbiota may cause immune activation, leading to disruption of the gut barrier.…”
Section: Discussionmentioning
confidence: 99%
“…However, research by Guo et al suggested that IBS is significantly associated with MS and its components, and thus it could be beneficial to address IBS symptoms while aiming for MS prevention (49). A recent study by Bayrak also pointed to the significantly higher MS prevalence among IBS patients than controls (50). As both PCOS and IBS populations may be more prone to developing MS, patients presenting with both conditions could benefit from early MS diagnostics, prevention and management.…”
Section: Anthropometric Biochemical and Hormonal Profile Of Ibs-pcos ...mentioning
confidence: 99%